2007
DOI: 10.1090/s0002-9939-07-08829-6
|View full text |Cite
|
Sign up to set email alerts
|

Level algebras with bad properties

Abstract: Abstract. This paper can be seen as a continuation of the works contained in the recent article (J. Alg., 305 (2006), 949-956) of the second author, and those of Juan Migliore (math. AC/0508067). Our results are: 1). There exist codimension three artinian level algebras of type two which do not enjoy the Weak Lefschetz Property (WLP). In fact, for e 0, we will construct a codimension three, type two h-vector of socle degree e such that all the level algebras with that h-vector do not have the WLP. We will also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
35
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 13 publications
(37 citation statements)
references
References 12 publications
(10 reference statements)
2
35
0
Order By: Relevance
“…If we allow the socle degree to be large, we now show that pure O-sequences of any codimension can be non-unimodal with arbitrarily many peaks. This result answers positively Question iii) (section 6) of [9]. Proof.…”
Section: Moreover If Equality Holds In Some Degree J Then It Holds supporting
confidence: 64%
See 4 more Smart Citations
“…If we allow the socle degree to be large, we now show that pure O-sequences of any codimension can be non-unimodal with arbitrarily many peaks. This result answers positively Question iii) (section 6) of [9]. Proof.…”
Section: Moreover If Equality Holds In Some Degree J Then It Holds supporting
confidence: 64%
“…Another challenge is to find the smallest socle degree for which a non-unimodal example exists. The best example of which we are aware is Example 5.1 of [9], where it is shown that h = (1,3,6,10,15,21,28,33,36,37,36,36,37) is a pure O-sequence; notice that this has socle degree 12.…”
Section: Moreover If Equality Holds In Some Degree J Then It Holds mentioning
confidence: 99%
See 3 more Smart Citations